STRATEGI OPTIMALISASI PEMBERDAYAAN SUMBER DAYA MANUSIA MENUJU SEKOLAH UNGGULAN DI MAN 2 KOTA PROBOLINGGO - Cahyaning Tiyas, Mutiah; Indiarti, Kinanti; Hasbullah Marzuki, M.; Putri Susanti, Anindya; Jadid Khadavi, M (As-Sulthan Journal of Education, 2024)
This study aims to analyze the strategies for optimizing human resources at MAN 2 Kota Probolinggo to achieve the status of an outstanding school. In modern education, strengthening human resources is crucial to face the challenges of globalization and technological advancement. The research method used is qualitative, with data collection through in-depth interviews and participatory observation involving the Head of the Madrasah, Public Relations, and teachers. The data obtained were analyzed using thematic analysis techniques to identify themes relevant to human resources empowerment strategies. The results indicate that MAN 2 Kota Probolinggo implements various human resources empowerment strategies, including continuous training, developing learning technologies, and reinforcing Islamic values. Routine training held at least twice a year focuses on improving pedagogical skills and technological proficiency, which are essential in adapting to competency-based curriculum changes. Additionally, collaboration with higher education institutions and training agencies plays a significant role in enhancing educators' competencies. Students' success in academic and non-academic competitions reflects the effectiveness of the strategies applied. With strong moral and spiritual support from teachers, students of MAN 2 have achieved accolades in various competition levels.